Дослідження пам'ятки чорної металургії салтівської культури - Колода, В.В. (Археологія, 1996)
Стаття присвячена дослідженню ремісничого центру лісостепового населення салтівської культури. Матеріали свідчать про розвинуте металургійне виробництво, поряд з яким існувало виготовлення гончарного посуду. Черная металлургия была одним из важнейших занятий населения салтовской лесостепи, о чем свидетельствуют как материалы ремесленного центра в урочище Роганина, так и аналогии на Белгородщине (Ездочное, Ютановка) и Харьковщине (Новая Покровка, селище-2 близ Волчанского городища, Старый Салтов). Сочетание выплавки железа с развитым гончарством свидетельствует о неполном выделении железоделательного производства (для населения данного памятника) в самостоятельную отрасль хозяйства. В данном случае налицо лишь территориальное обособление этого вида деятельности, что указывает и на тенденцию к социальному обособлению. Дополнительный интерес вызывает и тот факт, что находясь на границе степи и лесостепи мастера Роганинского центра имели экономические связи и с кочевым, и с оседлым миром салтовцев. The ferrous metallurgy was one of the most important works for population to the Saltovian forest-steppe, which is confirmed both by findings of the craft centre in the Locality Roganina and by analogues in the Belgorod district (Ezdochnoe, Yutanovka) and in the Kharkov region (Novaya Pokrovka, settlement-2 near the Volchansk city, Stary Saltov). Combination of iron melting and developed pottery shows that iron melting at that time and for population of that region did not exist as a completely independent branch of their economy, That type of activity was only territorially isolated, which demonstrates also the tendency to social isolation. It is also interesting that living on the border between the steppe and the forest-steppe, the craftsmen from the Roganino centre maintained economic relations both with nomadic and with the settled population of Saltov.